Przygotowania jezuickiej misji w Etiopii w świetle listów św. Ignacego Loyoli - Danieluk, Robert (Annales Missiologici Posnanienses, 2016)
The mission in Ethiopia was one of the first missionary endeavours of the Society of Jesus. Thus, Saint Ignatius of Loyola, the Founder of the Order, gave to its preparation special attention as shown in his numerous letters. The article briefly recalls the historiography and the genesis of this mission in order to summarize the content of the most important of the Loyola’s letters in what concern the origins of this missionary enterprise and the strategy to be adopted by the Jesuits sent to Ethiopia.